التأصيل الفقهي لبيع المعاطاة: Basis of Islamic Jurisprudent For The Sale of Conduct - Muhammad Abdo, Ahmad; Haji Abdullah, Luqman; Ali, Abdul Karim (Online Journal of Research in Islamic Studies, 2020)
Sale by mu’athah (conduct) is among the common practice now days and the jurists disagree on its permissibility. This paper will be focusing on this issue to see from the perspective of its fiqh origin and the points of the disagreement among the jurists. This study which is analytical in nature find that evidences show that this kind of sale is valid and it goes back to the maxim that the original nature of contracts are permissible in the absence of evidences from the Al Quran, Al Hadith or consensus. In the case of sale there is no clear evidence on the condition of the expressed declaration (sighat). The only condition is that it must be on mutual agreement. Hence any sign of mutual agreement between the parties the sale is considered valid and this can be measured by the custom (‘urf).